Essential strategies for financial services compliance - Mills, Annie; Haines, Peter 1959- (West Sussex, [England] John Wiley & Sons Ltd, 2015)
"A fully updated edition of the definitive guide to financial regulation In recent years, not only has the compliance field become firmly established, but it has seen staggering growth, thanks to never-ending changes in the regulatory environment. As regulation increases still further, the demand for clear guidance on navigating daily compliance issues is greater than ever. Now in its second edition, the highly successful Essential Strategies for Financial Services Compliance has been updated with the latest compliance strategies and regulatory information, making it indispensable for compliance officers, legal firms, and anyone else working with the financial services compliance function. Non-compliance represents a significant material risk for any financial services firm that fails to understand and appropriately apply regulatory standards. This Second Edition of Essential Strategies for Financial Services Compliance makes it easy to digest complex information on the regulatory framework. But this book is far from solely theoretical. A balanced approach means that both the concepts and their application are within reach. Annie Mills and Peter Haines deliver solid advice that can be applied on a day-to-day basis to manage any compliance issues that may arise. Read this book to: Understand the conceptual basis of compliance and the current regulatory environment applicable to the financial services industry Quickly and thoroughly learn the accepted best practices for everyday compliance Get up to date information on the current financial regulatory environment with this new edition Reference detailed advice as issues arise in day-to-day operations This update to the popular first edition of Essential Strategies for Financial Services Compliance will help eliminate non-compliance risk and ensure that your firm is entirely current on its ability to navigate the maze of financial services regulation"--Provided by publisher.
The UK regulatory environment -- The compliance function -- The compliance contract -- Mapping your compliance universe -- Mapping your corporate universe -- Regulators and other industry bodies -- The legislative environment and rules mapping -- Financial products, services, and documentation -- Compliance outside the compliance department -- Key compliance department activities -- Comply or die : when things go wrong.
Includes index.
Keywords: Financial services industry -- Law and legislation -- Great Britain; Corporate governance -- Law and legislation -- Great Britain; Ethics and compliance officers -- Great Britain -- Handbooks, manuals, etc